Improvement of sandy soil productivity with chicken manure treatment and NPK fertilizer for eggplant plants - Saijo, Saijo (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2024)
The aim of the research was to test and analyze the effect of chicken manure doses and NPK doses on the growth and yield of purple eggplant plants (Solanum melongena L) on sandy soil. Carried out at the Research Garden of the Faculty of Agriculture, Muhammadiyah University of Palangkaraya, Palangka Raya City, Central Kalimantan. The research period is June-September 2023 using a completely randomized design with two treatment factors. The first factor is the provision of 3 levels of chicken manure and the second factor is 3 levels of NPK treatment. Each was repeated 3 times, totaling 27 experimental units. The results of the research can be concluded that the effectiveness of the treatment dose of chicken manure influences the growth variables (plant height, stem diameter, number of leaves), namely at the treatment dose of chicken manure 30 t ha-1. The NPK dosage treatment had an effect on the yield components, both fresh fruit weight and harvest index, namely at an NPK dosage of 400 kg ha-1. In the yield component variable, the highest fruit weight was 297 g plant-1.